Pengaruh Brand Image dan Perceived Quality Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Honda Vario (Studi Kasus Pada Pengguna Honda Vario di Kota Semarang) - Inti Megadewi (Universitas Diponegoro, 2017)
Automotive industry development in indonesia very rapidly including motorcycle industry. Honda motorcycles issued its pedestal automatic motorcycles with the name Honda Vario. Loyalty consumers occurred because consumers feel satisfied , customer satisfaction can be influenced by the brand image that well as guaranteed perceived quality. Problems in this research is the declining sales of Honda Vario in 2015 within the Semarang City. The research results show that there is influence between the brand image to customer loyalty through customer satisfaction correlation obtained the results of 0,769. While the influence perceived quality of customer loyalty through customer satisfaction correlation obtained the results of 0,808. Then, in the analysis sobel test by using preacher tool, there is influence of intervening customer satisfaction in relations brand image and perceived quality of customer loyalty in Honda Vario.